YOU MADE THIS? I MADE THIS: CULTURES OF AUTOMATIC (MIS)ATTRIBUTION ON TIKTOK - Valdovinos Kaye, David Bondy; Rodriguez, Aleesha; Wikstrom, Patrik (AoIR Selected Papers of Internet Research, 2020)
In 2019, TikTok captivated international attention as a breakout short-video platform. A key affordance for user-generated content creators on TikTok is how easy the platform makes reproducing popular videos. The video creation interface allows users to make new videos based on the one they were just watching with just one tap. While these features make it fun and easy for users to replicate popular videos, it can also obscure the identity of the creators who created the ‘original’ content being reused. In this way, TikTok engenders a culture of misattribution. Users can freely reuse popular formats, audio clips, or even licensed music without any connection to the original source with impunity. Using a combination of an app walkthrough, a bespoke data scraping tool, content analysis, and a series of qualitative case studies, this study explores the contradictory logic of authorship and how (mis)attribution is shaping cultural production and platform practices on TikTok.